Studi Eksperimental Capillary Rise Material Karbon Aktif Bambu Betung dengan Variasi Temperatur Karbonisasi Sebagai Material PAD Sistim Direct Evaporative Cooling - Ramadana, Ketut Arpin; Wijaksana, Hendra; Komaladewi, A.A.I.A.S. (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstract The use of compressor-based air conditioning technology, better known as air conditione (AC), has triggered an increase in the overall use of electrical energy, also accompanied by an increase in the environmental impact it causes as a result of the use of refrigerants that are not environmentally friendly. As an alternative cooling, the researchers developed an evaporative cooling system based on air contact with water as a cooling medium.This study used carbonized and activated bamboo betung as a material for the DEC system. The research was conducted to obtain carbonized capillary rise material for bamboo betung at various temperatures of 400°C, 500°C, 600°C, 700°C dan 800°C then activated at 600°C with a holding time of 60 minutes.Based on the results of the capillary rise research, the active carbon material of bamboo betung BBKA 860 has the highest capillary rise height of 5.98 m with a pore size of 2.43 ?m (smallest). Meanwhile, the lowest capillary rise height was achieved by the BBKA 460 activated carbon material of 2.52 m, where this material has the largest pore radius of 5.76 ?m Keywords: Direct evaporative cooling,Material Pad,Bamboo Betung, Capillary rise